Working Towards the Development of an Online Intervention for Cyberaggression Behaviours: A Research Focus on Perpetrators’ Motivational Factors - Howman, Hannah Elizabeth (2023)
Background: Advancements in digital technologies have seen computer-mediated communication (CMC) become an integral part of modern culture. However, the emergence of CMC coincided with the ‘online disinhibition effect’, where people engage in social interactions online, with their behavioural inhibitions lowered. This has led to people engaging in cyberaggression behaviours, including cyberbullying, cyberstalking, and trolling, where people can partake in these behaviours due to a variety of motivational factors. However, research has demonstrated conflicting views of whether cyberbullying, cyberstalking, and trolling are three distinct behaviours, or whether they can be operationalised together under the term ‘cyberaggression’.